Image-Based Virtual Clothing - Harshada Kudtarkar; Dinesh Farad; Ruchira Zope; Dhanashree Hadsul (International Journal of Engineering and Management Research, 2021)
Online shopping has found speedy growth for the fast-paced world in the present situation. Precisely garments shopping are one of the most exciting parts especially for ladies. The continuous changing fashion and newly designed outfits motivates customers for shopping. New online shopping stores have added an ease for shopping your desired products by removing the constraints of places and time limits. As far as garments are concerned, predicting the appropriate size and imaging the real life look of that garment just by viewing its image is a challenging task. The project introduces an easy and feasible solution for the online shopping try-on scenario by introducing an app with a digital try-on feature. It can enhance online shopping experience. In this project, we propose an idea for fitting a given 3D garment model on a person. We will use 3d models of the clothes that will fit on the image of the user and enable a user to see himself/herself wearing virtual clothes. The 3D models of the clothes are stored in the system. On opening the application, user can view the clothes available and by using the mobile’s camera the user can get an idea of how the garment will fit on him/her. This way the user can have a fair idea about the look of the garment.